The banshees of Inisherin [videorecording (DVD)] - McDonagh, Martin; Farrell, Colin, 1976-; Gleeson, Brendan; Condon, Kerry, 1983-; Keoghan, Barry, 1992- (Searchlight Pictures, 2022)
Two lifelong friends find themselves at an impasse when one abruptly ends their relationship, with alarming consequences for both of them.